2012
DOI: 10.1007/s10549-012-2006-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent germline mutations in BRCA1 and BRCA2 genes in high risk families in Israel

Abstract: The spectrum of germline mutations among Jewish non Ashkenazi high risk breast/ovarian cancer families includes a few predominant mutations in BRCA1 (185delAG and Tyr978X) and BRCA2 (8765delAG). A few additional recurring mutations [A1708E, 981delAT, C61G (BRCA1) R2336P, and IVS2 + 1G > A (BRCA2)] have been reported in Jewish non Ashkenazi families. The 4153delA*BRCA1 C61G*BRCA1 and the 4075delGT*BRCA2 has been reported to recur in Russian/Polish non Jews and Ashkenazim, respectively. The rate of these recurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The Oncogenetics Unit recruited women who were counselled and genotyped for being at high risk for developing breast/ovarian cancer as determined by standard criteria (Laitman et al, 2012) and were subsequently found to harbour either a BRCA1 or BRCA2 mutation (see below). The Oncogenetics Unit recruited women who were counselled and genotyped for being at high risk for developing breast/ovarian cancer as determined by standard criteria (Laitman et al, 2012) and were subsequently found to harbour either a BRCA1 or BRCA2 mutation (see below).…”
Section: (I) Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Oncogenetics Unit recruited women who were counselled and genotyped for being at high risk for developing breast/ovarian cancer as determined by standard criteria (Laitman et al, 2012) and were subsequently found to harbour either a BRCA1 or BRCA2 mutation (see below). The Oncogenetics Unit recruited women who were counselled and genotyped for being at high risk for developing breast/ovarian cancer as determined by standard criteria (Laitman et al, 2012) and were subsequently found to harbour either a BRCA1 or BRCA2 mutation (see below).…”
Section: (I) Study Participantsmentioning
confidence: 99%
“…(ii) Analysis of the predominant Jewish mutations in the BRCA1/BRCA2 genes Mutational analyses for two of the three founder mutations (185delAG in BRCA1 and 6174delT in BRCA2) were carried out by restriction enzyme digest of PCR products, and analysis of the digested PCR products on agarose gels as previously described by us (Laitman et al, 2012). For each of these mutations, a known mutation carrier was used as a positive control in each experiment and each mutation was confirmed by sequencing.…”
Section: (I) Study Participantsmentioning
confidence: 99%
“…BRCA2 c.3847_3848delGT (4075delGT, rs80359405) pathogenic mutation causes frameshift and generates mutant p.V1283fs * 2 protein. This type of BRCA2 mutation is uncommon among the Ashkenazi population [11] but is quite widespread in northern and western Europe, being one of five most frequently observed mutations. In 26 Lithuanian families, Rebbeck et al [6] described 11 unique mutations, and the five most frequently observed BRCA2 mutations included c.658_659del (13), c.3847_3848del (4), c.6580dup (1), c.6410del (1) and c.7879A>T (1).…”
Section: Discussionmentioning
confidence: 99%
“…At initial diagnosis germline DNA from each patient was subjected to both BRCA1 and BRCA2 sequence analysis by BRACAnalysis CDx™ test for clinical evaluation which was performed by Myriad Genetic Laboratories (Salt Lake City, UT); or mutational analyses which were carried out by restriction enzyme digest of PCR products, to introduce a restriction site that distinguishes between the wild type and the mutant allele and analysis of the digested PCR products on agarose gels as previously described . The mutation resulted in a different fragment pattern from the wild type allele.…”
Section: Methodsmentioning
confidence: 99%